A Bank Muamalat's Resilience: The Role of Funding Policy in Overcoming Economic Challenges: Ketahanan Bank Muamalat : Peran Kebijakan Pendanaan Dalam Mengatasi Tantangan Ekonomi - Putri, Rizka Sabila; Hana, Kharis Fadlullah (Program Studi Ekonomi Islam, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng, 2024)
This research aims to analyze the resilience of Bank Muamalat in facing economicchallenges, as well as the role of funding policies in overcoming these challenges. The researchmethod employed is a descriptive qualitative approach with a case study on the Kudus BranchOffice of Bank Muamalat. Data was collected through interviews with relevant parties at the bank,direct observation, and literature review.The results show that Bank Muamalat implements strict credit analysis through a multistage screening process to avoid default risk. During economic crises, financing requirements weretightened and only provided to customers with fixed incomes from reputable companies. Economicand market conditions were continuously monitored to evaluate and adjust funding policies,including financing requirements. In managing liquidity, Bank Muamalat collaborated withvendors, particularly for large withdrawals, taking into account insured cash limits. Compliancewith regulations from the Financial Services Authority (OJK), Bank Indonesia (BI), and internalStandard Operating Procedures (SOPs) was a priority in funding and operational management.Product innovations such as the Prima Berhadiah Savings were also introduced to raise publicfunds. This research provides a deeper understanding of Bank Muamalat's resilience in facingeconomic challenges, as well as the role of the implemented funding policies. These findings canserve as input for Bank Muamalat and regulators in enhancing the resilience of Islamic banks inthe future.